Answer with explanation:
The Normalization Principle states that
![\int_(-\infty )^(+\infty )f(x)dx=1](https://img.qammunity.org/2020/formulas/physics/college/buhu3wjiia94t7ukkbwquaqhs639jgu6d3.png)
Given
Thus solving the integral we get
![\int_(0 )^(+\infty )A\cdot xe^(-kx)dx=1\\\\A\int_(0 )^(+\infty )\cdot xe^(-kx)dx=1](https://img.qammunity.org/2020/formulas/physics/college/lzgr66v0yr3oxic5p6x734ii5b2bxi922f.png)
The integral shall be solved using chain rule initially and finally we shall apply the limits as shown below
![I=\int xe^(-kx)dx\\\\x\int e^(-kx)dx-\int (d(x))/(dx)\int e^(-kx)dx\\\\-(xe^(-kx))/(k)-\int 1\cdot (-e^(-kx))/(k)\\\\\therefore I=(e^(-kx))/(k)-(xe^(-kx))/(k)](https://img.qammunity.org/2020/formulas/physics/college/xlgegauzzk11dkwgkkrs8w8wxe83o2cq42.png)
Applying the limits and solving for A we get
![I=(1)/(k)[(1)/(e^(kx))-(x)/(e^(kx))]_(0)^(+\infty )\\\\I=-(1)/(k)\\\\\therefore A=-k](https://img.qammunity.org/2020/formulas/physics/college/1riiwbalf0qpx2c6i5h7yxzo886p0vo9fe.png)